NPN Sziklai pair small-signal amplifier for high gain low noise submicron voltage recorder - Sachchida Nand Shukla; Syed Shamroz Arshad; Geetika Srivastava (Institute of Advanced Engineering and Science, 2022)
Small signal-to-noise ratio (SNR) and multiple noise sources, coupled with very weak signal amplitudes of bio signals make brain-computer interface (BCI) application studies a challenging task. The front-end recorder amplifiers receive very-weak signal (few μV) from high impedance electrodes and for efficient processing of such weak and low frequency (